Fenomena Super App Sebagai Suatu Layanan Digital Perbankan Ditinjau Dari Aspek Sosiologi Hukum - Eva Novelia Fauzia (CV. ITTC INDONESIA, 2025)
The development of information technology and the Covid-19 pandemic have accelerated digital transformation in the banking sector, one of which is through the emergence of super apps that integrate various financial features into a single platform. This innovation facilitates faster and more efficient transactions for customers but also presents challenges such as cybersecurity risks, data breaches, and technological misuse. A phishing case involving an APK file highlights the urgency for adequate legal regulation. In response, the Financial Services Authority (OJK) issued Regulation No. 21 of 2023 as the legal basis for digital banking services. This study uses a normative juridical and socio-legal approach to analyze the relationship between digital banking transformation and changes in societal behavior. The findings show that the super app is a technological adaptation to modern consumer needs, requiring comprehensive legal oversight.